Ornamentation and Islamic Identity in Contemporary European Mosques: An Analysis of Cultural, Aesthetic, and Functional Dimensions and Modern Influences - Haifa Ebrahim Al Khalifa; May Walid Lafi (Buildings)
Islamic ornamentation is important to mosque architecture, reflecting Islamic culture’s rich traditions and artistry. In contemporary European mosques, the challenge lies in combining these traditional styles with modern architectural designs, creating spaces that honor heritage and foster inclusivity among varied Muslim communities. These challenges impact mosque design’s cultural, esthetic, and functional dimensions, essential for sustaining Islamic identity. To explore how these factors influence cultural architectural expressions, this study examines ornamentation in four contemporary European mosques: Cologne Central Mosque (Germany), Cambridge Central Mosque (United Kingdom), Al-Ándalus Mosque (Spain), and Rijeka Mosque (Croatia). It evaluates their impact on cultural heritage, esthetic appeal, functionality, and Islamic identity within the context of modern architectural styles through a comparative analysis. The results demonstrate adaptations to local contexts and modern trends. Al-Ándalus Mosque reveals a strong identity by preserving traditional heritage, while Cologne and Cambridge Mosques balance tradition and modernity. Rijeka Mosque, heavily influenced by minimalism, reduces cultural richness despite a contemporary approach. Modern innovations like sustainable materials enhance functionality but sometimes dilute Islamic identity. The study concludes that integrating traditional elements with modern esthetics and functionality is essential to aligning mosque design with contemporary styles, while preserving Islamic identity and fostering a sense of belonging within Muslim communities in Europe.